Correlation Between The Attitude Of Religious Tolerance Educators With Religious Intolerance Of Learners - Muhammad Ikhza Helmy Nugroho; Sugeng Bayu Wahyono (STAI Hubbulwathan Duri, 2023)
Indonesia is a pluralistic country that has religious, linguistic and cultural diversity, if without good tolerance management it will have the potential to cause disputes in society, especially the religious sector because religion is a guideline for people's beliefs. So that there is a need for religious tolerance in society, there are many studies that examine the level of religious tolerance in schools, but there is no research that discusses the relationship between educators' religious tolerance and students' religious intolerance. This research is important to be carried out to find out whether there is a relationship. The question of this research is how to interpret the religious tolerance attitude of educators and students' religious intolerance at MTsN 1 Surabaya city?. How is the relationship between the religious tolerance of educators and the religious intolerance of students at MTsN 1 Surabaya? The purpose of this study was to determine the understanding of the religious tolerance of educators and the religious intolerance of students at MTsN 1 Surabaya City and to determine the relationship between the two attitudes. This is a quantitative research with correlation method with analytical technique, namely product moment statistic. The results of the study, namely, the attitude of religious tolerance of educators obtained a coefficient value that was categorized as